2003
DOI: 10.1034/j.1600-0463.2003.t01-1-1110208.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the use of proliferation markers in canine neoplastic and non‐neoplastic tissues: comparison of KI‐67 and proliferating cell nuclear antigen (PCNA) expression versus in vivo bromodeoxyuridine labelling by immunohistochemistry

Abstract: In order to evaluate the suitability of Ki-67 and proliferating cell nuclear antigen (PCNA) for determination of proliferative activity, the immunohistochemically determined nuclear expression of these antigens in canine non-neoplastic and neoplastic tissues was compared with the results of in vivo bromodeoxyuridine (BrdU) labelling, which - by measurement of the fraction of S-phase cells - is considered as the standard in the analysis of proliferative activity. The samples investigated consisted of non-neopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
0
7

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 35 publications
7
52
0
7
Order By: Relevance
“…More recently, other authors have tried to relate cell proliferation markers with the diagnosis, prognosis and outcome of breast neoplasms (Pena et al 1998, Zacchetti et al 2003, Kushlinskii et al 2004, Zuccari et al 2004, Nowak et al 2006. Nowak et al (2006) confirmed the relationship between Ki-67 and PCNA.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, other authors have tried to relate cell proliferation markers with the diagnosis, prognosis and outcome of breast neoplasms (Pena et al 1998, Zacchetti et al 2003, Kushlinskii et al 2004, Zuccari et al 2004, Nowak et al 2006. Nowak et al (2006) confirmed the relationship between Ki-67 and PCNA.…”
Section: Discussionmentioning
confidence: 99%
“…16,25,28,30,31,37,38,44 Ki-67 expression is a useful prognostic indicator in canine mast cell and mammary tumors. 30,38 In canine lung cancer, adenosquamous and squamous cell carcinomas differed from the other histologic types in having significantly higher proliferation indices.…”
Section: Discussionmentioning
confidence: 99%
“…As we expected, the number of Ki-67 positive cells significantly exceeded the amount of BrdU positive cells, which may result from the different nature of these markers. While Ki-67 is a nuclear protein naturally occurring in cells with a potential to divide and is present in all phases of the cell cycle except the phase G0 and the beginning of the G1 phase [30], BrdU only labels cells undergoing DNA synthesis [31]. Indeed, occurrence of BrdU-labeled cells in the CC region in our experiment was very rare in all investigated sections, which was also previously demonstrated using a multiple BrdU labeling in cervical, thoracic and lumbar spinal cord [9].…”
Section: Discussionmentioning
confidence: 99%